Plan de Marketing para la Comercialización de Ropa Industrial Producida en el Taller de Corte y Confección del Centro del Muchacho Trabajador ubicado en la Ciudad de Quito, Teniendo como Meta el Desarrollo Económico y Social de sus Miembros - López Pezantes, Raquel Paulina (2015)
This research entitled "Marketing Plan Marketing for Industrial Clothing produced in the workshop Dressmaking of Working Children Center located in the city of Quito, with the goal of economic and social development of its members" is a contribution to both making workshop, as the institution in general have continued growth and according to market demands, knowing they have the resources to do so, thus achieving the main objective of the institution, which is pursue economic, social and professional of each of the members of this large family development. A comprehensive description of all you have is presented and offers Working Children Center to society, mentioned what types of workshops and products offered in each of these, and the work is mentioned that the institution has been developing throughout these years.